Manajemen Konflik: Tinjauan Sumber dan Tingkatan Konflik - Mohammad Akbar Nur Wachid; Fajrin Afandi; St. Nur Azizah; Ulfia Rhodhotul Jannah; Mu’alimin Mu’alimin (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Conflict is a universal phenomenon that emerges in various aspects of life, ranging from education, social interactions, and law to ecological systems. Its complex dynamics require a deeper understanding of both the underlying sources and levels of conflict to enable constructive management. This study aims to systematically review the literature on conflict with a focus on two key aspects: *sources of conflict* and *levels of conflict*. The method employed is a literature review by searching articles through Google Scholar and Publish or Perish (PoP) using the keywords “sources of conflict” and “levels of conflict.” From an initial pool of 30 articles, screening was conducted based on relevance, recency (2019–2025), and open access availability. The final selection yielded 7 articles for in-depth analysis. The findings indicate that sources of conflict include internal factors (psychological, values, communication), external factors (ecological, socio-cultural), and structural dimensions (legal, political). Levels of conflict were identified at the intrapersonal, interpersonal, group, and structural levels. This review highlights that conflict is a multidisciplinary phenomenon requiring integrative examination. The implications suggest the need for developing a cross-disciplinary conceptual framework to understand conflict comprehensively and to provide a stronger basis for more effective resolution strategies.